Time Control Analysis of the Construction of the Joyoboyo Intermodal Terminal Pedestrian Tunnel to the Surabaya Zoo - Sartiyana, I Ktut Riagung; Nugroho, Laksono Djoko; Muhammadun, Haris (Transpublika Publisher, 2025)
The primary objective of this research is to examine the timeline for the construction of a pedestrian tunnel connecting the Joyoboyo Intermodal Terminal (TIJ) with the Surabaya Zoo (KBS). The construction of this tunnel is considered a crucial project aimed at enhancing accessibility and alleviating congestion along the Joyoboyo road. The estimated cost for this project is Rp 31,996,921,529.00 and it is scheduled to be completed within 135 calendar days. The results showed that the main factors of project delays were due to delays in the procurement of 40cm diameter piles, interference due to inundation due to undetected PDAM pipes. Using the CPM method, the identification of the critical trajectory enabled the optimisation of the project duration and reduced the risk of delays. In addition, incremental cost analysis showed the relationship between time acceleration and increased project cost. By identifying key factors causing delays and implementing strategic planning methodologies such as the CPM, the project was able to enhance efficiency and mitigate potential setbacks. Furthermore, the study shed light on the economic implications of time acceleration, emphasizing the importance of balancing speed with cost considerations in construction projects.